Postpartum Mother Psychosocial Conditions With Covid-19 Isolation - Marilin Diah Astuti; Sri Mintasih (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Postpartum mothers with COVID-19 isolation can experience feelings of anxiety about being infected and afraid of death, loneliness, loss and sadness so that it can have an impact on the mother's psychosocial condition which can increase to stress and trauma, confusion and anger due to having to undergo the delivery process and self-isolate without family support, Not allowed to be visited or meet anyone. If this condition is allowed to continue without proper treatment, it can result in a psychotic condition Objectives: To identify maternal psychosocial conditions in postpartum mothers in the COVID 19 isolation room Methods: 100 postpartum mothers who were selected according to inclusion and exclusion criteria. The instrument used was a questionnaire on the characteristics of the respondents; the social support questionnaire which is a modification in the Indonesian language of the postpartum support system questionnaire and the family coping questionnaire; and a questionnaire to measure maternal psychosocial conditions using the Edinburgh Postpartum Depression Scale (EPDS). Results: A total of 43% of mothers experienced psychosocial problems, namely major depression. Factors associated with postpartum maternal psychosocial conditions with COVID19 isolation were work, economic status, parity status and social support (p <0.05). The factor that most influenced maternal psychosocial conditions in postpartum mothers with COVID 19 isolation was social support (OR 4.024; 95% CI; 1.601-10.112) Conclusion: Social support is a dominant factor affecting postpartum maternal psychosocial conditions.